Creation the Site-Quest by using the Cloud Services: From the Experience of Teaching Future Teachers - Khmil, Nataliia; Morkvian, Iryna; Kyselovа, Olesia (My University, 2020)
The paper highlights the author's experience of teaching future teachers the creation of a site-quest by using cloud services. Referring to the understanding of the concept of "web-quest", the explanation of "site-quest" is defined. The methodology of teaching future teachers about the creation of a site-quest by using cloud services is offered. Possible methods of their application for the organization of student work during the development of model and structure of the site-quest, didactic materials (mind maps, virtual boards, clouds of words, interactive exercises, etc.) and it is filling out are indicated. The experience of implementation of the described methodology on the example of creation by the future teachers of the site-quest "School of young programmers" in the lessons of the discipline "Cloud technologies in the educational process" is presented.
Khmil N. Creation the Site-Quest by using the Cloud Services: From the Experience of Teaching Future Teachers / N. Khmil , I. Morkvian, O. Kyselovа // CEUR Workshop Proceedings, 2020. – Vol. 2732. – Р. 1164–1171.
Keywords: The paper highlights the author's experience of teaching future teachers the creation of a site-quest by using cloud services. Referring to the understanding of the concept of "web-quest", the explanation of "site-quest" is defined. The methodology of teaching future teachers about the creation of a site-quest by using cloud services is offered. Possible methods of their application for the organization of student work during the development of model and structure of the site-quest, didactic materials (mind maps, virtual boards, clouds of words, interactive exercises, etc.) and it is filling out are indicated. The experience of implementation of the described methodology on the example of creation by the future teachers of the site-quest "School of young programmers" in the lessons of the discipline "Cloud technologies in the educational process" is presented; site-quest; cloud services; creation of a site-quest; future teachers; сайт-квест; облачные сервисы; создание сайта-квеста; будущие учителя.